Multiethnic Society in the Concept of Transformational Justice: Case Study of Salatiga City - Martri Sonny; I Nyoman Nurjaya; Lucky Endrawati; Fachrizal Afandi (Audito Comparative Law Journal (ACLJ), 2023)
This study aims to see the harmony of diversity in Salatiga City using the concept of transformational justice. Transformational justice is a proposed type of justice model from F. Budi Hardiman, based on Derrida's theory of deconstructivism and Juergen Habermas's discourse theory. This is socio-legal research, studying law empirically by elaborating law with data in the form of observations, interviews, and documentation. The results of the study present what things make Salatiga City a Tolerant City. With the various results presented, the researcher then discussed them with Hardiman's perspective regarding the concept of transformational justice. The results of the study show that the transformative features of various elements in the society of Salatiga City in terms of pre-political social existence are not eliminated in public dialogue.